The Relationship of Budget Target, Budget Emphasis, and Ethics on Budget Gaps - Hidyatussadhikin, Jumadil Saputra, Murhaban, Rayyan Firdaus, M. Natsir Mahmud Nur, (Opción, 2019)
This study aims to determine the effect of budget target clarity, budget emphasis, and ethics on the budget gaps via a multiple linear regression analysis performed by using SPSS 23. The results indicate that budget target clarity and ethics has a significant negative effect on the budget gaps while the budget emphasis has a significant positive effect on the budget gaps. In conclusion, a good, specific and measurable budget target clarity can reduce the emergence of budget gaps in the SKPD of Lhokseumawe City.